Production of M-type strontium hexaferrite magnetic powder with the high-pure magnetite concentrate via the ceramic process. Issue 2 (3rd April 2022) - Zhou, Yujuan; Jiang, Tao; Xu, Bin; Lin, Yuming; Zhang, Min; Liu, Lanming; Zhong, Shouguo; Wei, Chengzhi; Chen, Yufeng; Yang, Yongbin; Li, Qian
ABSTRACT: The high-pure magnetite concentrate (HPMC) was studied for a substitution of iron scale to produce the magnetic powder of strontium hexaferrite via the conventional ceramic process in this work. The magnetic powder obtained under the optimum conditions had a magneto plumbite structure, which was confirmed by X-ray diffraction (XRD). Scanning electron microscope (SEM) depicted that ferrite grains were hexagon shaped and evenly distributed with an average particle size of about 1 μm. Furthermore, a comparison of magnetic powders separately produced with HPMC and iron scale was made by detecting the magnetic properties of their sintered magnets using a permanent magnetic measuring system. The results demonstrated that the HPMC magnetic powder had a superiority over iron scale magnetic powder, and it had fully achieved the level of Y30-1 product in China. In the final part, the economic feasibility of using HPMC for magnetic powder production was verified by the cost–benefit analysis.